1986
DOI: 10.1002/j.1460-2075.1986.tb04305.x
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific expression of a homeo box-containing gene in the non-segmented sea urchin embryo.

Abstract: Hybridization of Drosophila homeo box DNA probes to Southern transfers of genomic DNA from the Hawaiian sea urchin Tripneustes gratilla has revealed that the sea urchin genome contains at least five homeo boxes. Examination of the DNA from several individuals shows that the sequences flanking these homeo boxes exhibit little restriction fragment length polymorphism, indicating they are more highly conserved than the majority of sea urchin DNA. Several clones in a T. gratilla genomic DNA library which hybridize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 41 publications
2
43
1
Order By: Relevance
“…Several homeobox sequences have been found in different echinoid species (Dolecki et al 1986;DiBernardo et al 1994;Ruddle et al 1994;Dobias et al 1996;Popodi et al 1996). However, the function of these homeodomain proteins is not well understood in sea urchin development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several homeobox sequences have been found in different echinoid species (Dolecki et al 1986;DiBernardo et al 1994;Ruddle et al 1994;Dobias et al 1996;Popodi et al 1996). However, the function of these homeodomain proteins is not well understood in sea urchin development.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the single Hox gene complex of S. purpuratus contains 10 genes, and that among them, only two Hox genes (Hbox1 and Hbox7) are expressed significantly in sea urchin embryos (Arenas-Mena et al 1998). TgHbox1 (Dolecki et al 1986) and its ortholog, SpHbox1 ) are known to be expressed exclusively in the aboral ectoderm cells, and it has been suggested ) that Hbox1 genes could be involved in establishing the irreversible determination of aboral ectoderm. SpHbox7 transcripts are localized in oral ectoderm, endoderm, secondary mesenchyme cells (SMC; Dobias et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These transcripts code for various types of protein including proteins of the troponin C family (Bruskin et al, 1981), extracellular matrix proteins (Angerer et al, 1988;Nocente-McGrath et al, 1989), cytoskeletal actins (Lee et al, 1986), homeodomain containing proteins (Dolecki et al, 1986), cell surface proteins (Yang et al, 1989a), proteins involved in the building of the skeleton or specific to the micromere lineage (Grant et al, 1985;Benson et al, 1987;Harkey et al, 1988) and EGF-related proteins (Yang et al, 1989b). However, nearly all the transcripts so far characterized are specific to the late stages such as the mesenchyme blastula, gastrula or pluteus.…”
Section: Introductionmentioning
confidence: 99%
“…Derived amino acid sequences of P. japonica Hox-type genes were compared to those of Tripneustes gratilla (Dolecki et al, 1986;Dolecki et al, 1988;Wang et al, 1990), Paracentrotus lividus (Di Bernardo et al, 1994), Lytechinus variegatus (Ruddle et al, 1994), Heliocidaris erythrogramma (Popodi et al 1996), Hemicentrotus pulcherrimus (Ishii et al, 1999), Strongylocentrotus purpuratus (Martinez et al, 1999), Asterina minor (Mito and Endo, 1997), Oxycomanthus (Comanthus) japonicus, and Stegophiura sladeni (Mito and Endo, 2000). Multiple alignments and neighbor-joining analyses were performed using CLUSTAL W (Thompson et al, 1994).…”
Section: Sequence Analysismentioning
confidence: 99%